1989
DOI: 10.1136/bmj.298.6666.93
|View full text |Cite
|
Sign up to set email alerts
|

Life threatening interaction between tamoxifen and warfarin.

Abstract: This considerably reduced requirement for warfarin prompted a retrospective review of medical records at our hospital for the period 1981-6 to examine whether there might be an interaction between tamoxifen and warfarin. The records of women with breast cancer and a subsequent admission for a serious thromboembolism were examined. There were 18 such women: seven who had had deep venous thrombosis and 11 who had had a pulmonary embolus with probable deep venous thrombosis. Five of them were taking tamoxifen whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…Life-threatening interactions between tamoxifen and warfarin have been reported (Lodwick et al 1987;Ritchie & Grant 1989;Tenni et al 1989). This suggests that tamoxifen may inhibit warfarin metabolism, but this has not been properly documented and the clinical relevance of tamoxifen enzyme inhibition is unclear.…”
Section: Drug Interactionsmentioning
confidence: 97%
“…Life-threatening interactions between tamoxifen and warfarin have been reported (Lodwick et al 1987;Ritchie & Grant 1989;Tenni et al 1989). This suggests that tamoxifen may inhibit warfarin metabolism, but this has not been properly documented and the clinical relevance of tamoxifen enzyme inhibition is unclear.…”
Section: Drug Interactionsmentioning
confidence: 97%
“…A few previous studies found that estrogen can enhance the effect of warfarin [23,24]; it is, however, not known whether warfarin medication can affect the activity of estrogen, which may further affect the development of breast cancer. Tamoxifen can interact with warfarin by competition for plasma protein binding [25]; thus, patients with warfarin treatment may be prescribed less tamoxifen to prevent relapse of breast cancer compared to those without warfarin treatment. Patients with long-term medication of warfarin are recommended not to eat or eat less of foods that contain relatively a large amount of vitamin K, such as broccoli, spinach, soya bean products, and green tea [26].…”
Section: Discussionmentioning
confidence: 99%
“…Life-threatening interactions between tamoxifen and warfarin have been reported (LODWICK et al 1987;TENNI et al 1989;RITCHIE and GRANT 1989), but the underlying mechanisms are not clear. In these cases, co-administration of tamoxifen to patients who were adjusted to a stable prothrombin time with warfarin, led to a serious increase in prothrombin time.…”
Section: Drug Interactionsmentioning
confidence: 99%